Effect of the Power Balance® Band on static balance, hamstring flexibility, and arm strength in adults - Verdan, P. J. R.; Marzilli, T. S.; Barna, G. I.; Roquemore, A. N.; Fenter, B. A.; Blujus, B.; Cosselin, K. P. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to determine the effect of Power Balance® bands on strength, flexibility, and balance. Strength and flexibility were measured using the MicroFit system. Strength was measured via a bicep curl and flexibility via the sit-and-reach method. Balance was measured by the BIODEX System SD. There were 4 different conditions for the balance test: eyes open on a firm surface (EOFS), eyes closed on a firm surface (ECFS), eyes open on a foam surface (EOFoS), and eyes closed on a foam surface (ECFoS). There were 24 subjects in the study (10 men and 14 women). A counterbalance, double-blind, placebo, controlled within-subject design was used. Each of the subjects participated in 3 treatment sessions, consisting of Power Balance®, placebo band, and no band. An alpha level of p = 0.05 was set a priori. There were no significant differences in strength, flexibility, or balance with regard to the treatments used. There was a significant difference between the conditions in the balance test (p = 0.000): EOFS (0.51), ECFS (0.68), EOFoS (0.99), and ECFoS (2.18); however, these were independent of the treatment conditions. The results indicate that the Power Balance® bands did not have an effect on strength, flexibility, or balance.